Why do the children of young mothers have poorer outcomes? - Bradbury, B (My University, 2007)
Various data sources indicate that a mother's age at birth is a good predictor of later-life outcomes for both the mother and her child. Younger mothers are more likely to fare worse in socioeconomic outcomes than mothers who have delayed child bearing, and some studies have found that the children of younger mothers have fared worse from infancy and into their late teenage years. This presentation outlines some recent research studies, and uses data from the 'Growing Up in Australia, the Longitudinal Study of Australian Children (LSAC)', to predict the outcome index increase due to a mother being aged 30 rather than 20 at birth.
Keywords: Families -- Mothers; Families; Families and relationships; Families; Mothers; Families and relationships